Generic Implementation Framework approach for public private mix in Tuberculosis control at a private hospital in Gresik, East Java, Indonesia - Fahrudda, Ansarul; Kusbaryanto , Kusbaryanto (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Tuberculosis continues to be a concern at the global level. Indonesia is a high-burden country that keeps efforts through TB control programs by implementing a private-public mix (PPM) strategy. This study aims to analyze the implementation of PPM in a private hospital using the Generic Implementation Framework approach. Methods: This study conducted a mixed method approach including quantitative and qualitative analysis of data with explanatory sequential design. The analyzed variables were the assessment elements used in determining hospital accreditation, variables to get an overview of PPM, and achievement of indicators. Quantitative data were analyzed descriptively, while the qualitative with thematic analysis. Results: The quality of TB control at the hospital was under the accreditation standards. There was an increase in the number of patients treated but uptrend in the number of loss to follow-up patients in the last three years. The success rate of treatment in 2021 has not yet achieved as it was influenced by patients who were lost to follow-up and treatment failure. Supporting factors for the PPM implementation were the script of cooperation, commitment, cooperation, communication, mutual trust, maintained service quality, inter-dependence, and mutual benefit as inhibiting factors related to the management of treatment adherence. Conclusion: The achievement of program indicators has yet to meet the target. Therefore, it is necessary to evaluate regulations, standard operating procedures, and cooperation scripts to reach the standard.